The Critical Role of Nurses in Supporting Chronic Disease Patients Amid Crises - Emtenan Mshoor Alkhairi, Esraa Mohammed Alhazmi, Maram Ghazai Hammad Alharbi, Madhawi Falah Ayad Alharbi, Noora Ali Hussien Al Mukalas, Ghaliah Ali Hussien Almukalas, Nawir Ali Almadi, Fatimah Yahya Mohamad Farhan (Journal of International Crisis and Risk Communication Research, 2024)
Nurses are instrumental in chronic disease management even during the crunches when the healthcare systems are besieged and established patterns of care are dislocated. The present review explores how nurses facilitate the process of care continuity and maintenance of chronic disease patients focusing on their contributions to care coordination, education of patients and provision of psychosocial support. Integration of advanced technologies such as telemedicine, remote supervision and guided interaction by patients has expanded the horizons of nurses’ contribution improving both clinical outcomes and patient’s satisfaction level. This review also highlights the typical issues encountered by nurses, such as lack of resources and lack of ethics, which require certain level of perseverance and capability to maintain the quality of care in chaotic situations. Recent studies have demonstrated the usefulness of using nurse-led initiatives to decrease the need for hospitalizations, promote self-care activities and improve health outcomes of vulnerable communities. The results of the research indicate the necessity of transplantation into the frameworks of the healthcare new nursing concepts that will provide people with chronic diseases a full comprehensive, fair and viable healthcare anywhere and anytime.